Implementasi Kebijakan Program Lesson Study Berbasis Sekolah (LSBS) di MINU Trate Putri Gresik - Suyanik Suyanik; Erny Roesminingsih (Jurnal Paedagogy, 2021)
This research aims to describe the course of policy implementation Lesson Study, to know the things that support and are an obstacle in implementing policies and programs Lesson Study to determine the impact / results in implementing the policy program at the Lesson study MINU Trate Putri Gresik. This research uses Qualitative approaches, data collection technique through the process of observation, interviews, documentation, and questionnaires. Data analysis was performed based on four interrelated components, namely data collection, data reduction, presentation of data, the data inference. For overcome the obstacles that occur MINU Trate Putri always try to maximize all of the potential that exists. Among them is the rescheduling of any activity that is not done, the conversion or exchange of teaching hours to be optimal in the observation, as well as the fulfillment of all the necessary infrastructure. The impact of the implementation of the School-Based Lesson Study program includes a change in the paradigm of teachers in a more open, creative and collaborative learning process as well as increasing achievements that have been achieved by students, teachers and schools in general.